Profitability, Liquidity, Solvency and Activity Analysis to Assess Financial Performance of PT. Visi Media Asia Tbk. - Ikasanti, Putri Wahyu; Alwi, Alwi (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
The purpose of this research is to find out and analyze how big the financial performance of PT. Visi Media Asia, Tbk. In measuring the company's financial performance, the data analysis technique used is financial ratio panalysis which includpes 1). Profitability (Return on assets, Return on equity and Net profit margin) 2). Liquidity (Current ratio, Cash ratio and Quick ratio) 3). Solvency (debt to assets and debt to equity ratio) and 4). Activities (Total asset turnover and inventory turnover). using the One Sample T-test with the help of the SPSS Version 20 program. The sample used in this study is the financial statements in the form of balance sheets, income and cash flows for the last 10 years from 2015. 2011 – 2020. Based on the results of research and analysis shows that 1). Financial performance of PT. Visi Media Asia Tbk during 2011-2020 in terms of profitability ratios, the results of the study show that each of these indicators is considered not performing well. 2). Liquidity, the results of the study show that through the indicators of the current ratio and cash ratio, it is known that the financial performance of PT. Visi Media Asia Tbk, is considered not to perform well. Meanwhile, when viewed from the quick ratio, it is known that the financial performance of PT. Vision of Media Asia Tbk, which is considered to be performing well. 3). Solvency, financial performance research results show that each of these indicators is considered not performing well and 4). The results of the calculation of the activity ratio show that the financial performance of PT. Visi Media Asia Tbk, from each of these indicators is also considered not to perform well.